Auralization of railway noise: Emission synthesis of rolling and impact noise. (1st December 2017) - Pieren, Reto; Heutschi, Kurt; Wunderli, Jean Marc; Snellen, Mirjam; Simons, Dick G.
Abstract: Within the research project TAURA, a traffic noise auralization system was developed that covers road traffic and railway noise. This paper focuses on an emission synthesizer for railway noise and presents a concept for rolling and impact noise. The synthesis is based on a physical approach in which the noise generation mechanism is modeled in the time domain. As a starting point, equivalent roughness patterns of each wheel and the rail are generated. These spatial signals are used to implicitly model the mechanical excitation of the wheel/rail system. Transfer paths describing the vibrational behavior and the radiation of wheels and rail are implemented as digital filters. This approach features a high degree of flexibility but requires knowledge of the detailed model parameters.